1999
DOI: 10.1002/(sici)1097-0207(19991230)46:12<2027::aid-nme575>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

A finite element constitutive update scheme for anisotropic, viscoelastic solids exhibiting non-linearity of the Schapery type

Abstract: SUMMARYThis study presents a new scheme for performing integration point constitutive updates for anisotropic, small strain, non-linear viscoelasticity, within the context of implicit, non-linear "nite element structural analysis. While the basic scheme has been presented earlier by the authors for linear viscoelasticity, the present work illustrates the generality of the underlying fundamentals by extending to Schapery's non-linear model. The method features a judicious choice of state variables, a stable bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…The final consideration in this material constitutive model is the format of the nonlinear coefficients. Poons & Ahmad [ 40 ] showed that, for material with Schapery-type nonlinearity, the nonlinear coefficients in 3D cases can be taken as …”
Section: Materials Modelsmentioning
confidence: 99%
“…The final consideration in this material constitutive model is the format of the nonlinear coefficients. Poons & Ahmad [ 40 ] showed that, for material with Schapery-type nonlinearity, the nonlinear coefficients in 3D cases can be taken as …”
Section: Materials Modelsmentioning
confidence: 99%
“…Replacing the derivative by finite difference in equation (1), and using the backward Euler scheme, which is known for its stability, the following can be obtained 29 …”
Section: Seat-occupant Femmentioning
confidence: 99%
“…The Schapery model has been extensively applied to isotropic and anisotropic materials. Recently, numerical integration methods of the Schapery model and their implementations in finite element environment have caught much attention among researchers [13,14].…”
Section: ( ) J T δ -Simplified Multiple Integral Representationmentioning
confidence: 99%